(6-Hydroxy-2-{[2-(N-methylcarbamothiolyl)hydrazin-1-ylidene-kappa N-2(1),S]methyl}phenolato-kappa O-1)(triphenylphosphane-kappa P)nickel(II) chloride - Shawish, H.B.; Maah, Mohd Jamil; Ng, S.W. (International Union of Crystallography, 2010)
The deprotonated Schiff base ligand in the title salt, [Ni(C9H10N3O2S)(C18H15P)]Cl, functions as an N,O,S-chelating anion to the phosphine-coordinated nickel(II) atom, which exists in a distorted square-planar geometry. The hydroxy group forms an intramolecular O-H center dot center dot center dot O hydrogen bond. The two amino groups of the cation are hydrogen-bond donors to the chloride anion; the hydrogen bonds generate a chain structure running along the b axis.